Sustainability and governance - Lehman, Cheryl R. (Bingley, U.K. : Emerald, 2015)
Giving voice to the marginalized, broadly defined, is the aim of this volume in its examination of social life increasingly marked by global inequality and the extension of market rationalities to all arenas. Revealing the outcome to populations, stakeholders, and the environment when policies resting on narrowly constrained logics are employed, these researchers lead the way in probing accounting's participation in significant struggles of our times. In order to better appreciate the consequences of economic globalization, the works examine contemporary rhetoric, governance, politics, and strategies and the manner in which accounting technologies are integrated. These works maintain that transformation is inevitable and they search for possibilities of change that can be manifested in socially equitable practices and improved social justice by enhancing accountability.
Protecting the public interest through mandatory auditor firm rotation: a controversial issue / Jacqueline Burke, Haykin Lee -- Independent directors and dividen payouts in the post Sarbanes-Oxley era / Timothy Coville, Gary Kleinman -- Mandated climate change disclosures: a study of large US firms that emit carbon dioxide / Martin Freedman, Jin Dong Park, A.J. Stagliano -- Institutional accountability for true green / Fahrettin Okcabol, Joan Hoffman -- Are public university executives paid for their performance? / Theresa Henry -- Invited essay on gender and social justice: "Gender, knowledge and accountability" / Shana Penn.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Accounting -- Financial; Public finance accounting; Accounting; Corporate governance; Sustainability; Accounting -- Social aspects